2021
DOI: 10.1002/solr.202100106
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Inkjet‐Printed High‐Efficiency Perovskite Solar Cells: Manipulating the Spreading and Crystallization Behaviors of Picoliter Perovskite Droplets

Abstract: Drop‐on‐demand inkjet‐printing has the advantages of high cost‐effectiveness and powerful patterning ability, which can be a promising technique for perovskite pattern deposition. However, by far most of the reported works using inkjet‐printing for perovskite films fabrication are printing solvent‐rich wet precursor layers on the high‐temperature meso‐TiO2 substrate, and subsequently require a vacuum‐assisted thermal annealing process to enhance the crystallization of perovskite precursor, which largely elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…For the printable solar cells, various photoactive materials have been implemented in the literature including hybrid organic-inorganic materials like perovskites and organic conjugated polymer blends such as poly(3-hexylthiophene) (P3HT) (as being donor) and [6,6]-phenyl C61-butyric acid methylester (PCBM) (as being acceptor) [111][112][113][114]. Lab-scale investigations showed that printed perovskite solar cells can reach up to PCE values comparable with those of silicon solar cells, e.g., 16.6% PCE by Zhang et al [115], 17.2% PCE by Schackmar et al [116], 17.74% PCE by Li et al [117], stabilized PCE of 18.5% PCE by Eggers et al [118] and 19.6% by Li et al [119]. In addition to these developments, the printed organic cells developed by Liu et al [120] achieved 15% PCE.…”
Section: Energy Harvesting and Storagementioning
confidence: 99%
“…For the printable solar cells, various photoactive materials have been implemented in the literature including hybrid organic-inorganic materials like perovskites and organic conjugated polymer blends such as poly(3-hexylthiophene) (P3HT) (as being donor) and [6,6]-phenyl C61-butyric acid methylester (PCBM) (as being acceptor) [111][112][113][114]. Lab-scale investigations showed that printed perovskite solar cells can reach up to PCE values comparable with those of silicon solar cells, e.g., 16.6% PCE by Zhang et al [115], 17.2% PCE by Schackmar et al [116], 17.74% PCE by Li et al [117], stabilized PCE of 18.5% PCE by Eggers et al [118] and 19.6% by Li et al [119]. In addition to these developments, the printed organic cells developed by Liu et al [120] achieved 15% PCE.…”
Section: Energy Harvesting and Storagementioning
confidence: 99%
“…Unlike spin-coating, inkjet-printing led to the development of a discontinuous perovskite film on the m-TiO 2 layer, with large areas of the substrate being highly uncovered (bright area) by the perovskite structures (dark area). This could be the result of several interconnected reasons that are mainly related to the composition of the ink, the wetting of the substrate by the ink, as well as the printing parameters [16]. For the present study, a preliminary optimization of the printing parameters took place to achieve an equal thickness of both the perovskite absorbent layer achieved through inkjet-printing and the one produced by spin-coating (see Figure 3a,b), while the materials and fabrication conditions were attempted to be kept the same for comparison purposes.…”
Section: = Cos ⁄mentioning
confidence: 99%
“…The third level of optimization is related to the printing parameters, e.g., droplet volume and spacing, jetting velocity, and printing speed, where, in turn, their optimization is dependent on the formulation of the perovskite ink and the wetting of the substrate by the ink. Therefore, it is understood that the optimization of the whole printing process requires systematic and holistic engineering since the modification of one of the factors can influence all other parameters [16].…”
Section: = Cos ⁄mentioning
confidence: 99%
See 1 more Smart Citation
“…
The rapid chemistry and processing development along with exploring underlying fundamentals [1,2] have increased the performance of perovskite solar cells (PSCs) to over 25%, [3] making them a potential candidate for nextgeneration photovoltaics (PVs). PSCs consist of a photoabsorber film sandwiched between n-type and p-type charge transport films, [4] all shown to be solution processable and thus, fabricable using scalable depositions such as slot die, [5,6] gravure, [7] spray, [8] and inkjet-printing systems [9,10] through automated manufacturing. The deposition of thin films from solutions has been shown for the SnO 2 electron transport layer (ETL), perovskite, and carbon electrodes.
…”
mentioning
confidence: 99%